Machine Control and Multimedia Communication with Mini-PC - Haehnel, Hartmut Prof.Dr.-Ing. (International Journal of Online and Biomedical Engineering (iJOE), 2006)
The communication need in companies machines - and equipment construction constantly rises. Also small and medium-size enterprises act today more than ever on a global market. On the other hand the enterprises are at a substantial costing and time pressure by the globalization of the markets. Experts act in this connection increasingly in different locations. In the result of the current research in the context by the Federal Ministry for economics promoted of a co-operation of research project between the FH Duesseldorf, Labor for computer technology and the company Frölich & Klüpfel Druckluftechnik GmbH & CO. KG was determined that the industrielle use of Multimedia Communication for companies in the context of examined cases of application with a large use which can be expected is possible.